The Wedding of Stefan Mikołaj Branicki and Katarzyna Scholastyka Sapieha (1687): a Historical and Legal Approach - Łopatecki, Karol (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
This article analyzes civil law contracts relating to the wedding of Stefan Mikołaj Branicki and Katarzyna Scholastyka Sapieha. The marriage was concluded in 1687, and it was preceded by a prenuptial agreement a year before. A month after the wedding, on June 21, 1687 five documents were recorded in town books, which were analyzed by the author. A particular case was that the dowry has remained unpaid for 21 years. The lack of renunciation resulted in a meeting of the two houses – the Branickis and the Sapieha – in Zabłudów in order to carry out melioration. The dowry was raised from 200,000 to 324,000 zlotys, in return of which Katarzyna Scholastyka was to renounce the rights to her paternal and maternal estates. The author emphasizes that as early as the 1690s, the Sapiehas helped the Branickis to enter in possession (as pledgees) of the Orla estate, which was a certain compensation for the delay in paying the dowry. However, until 1720 (i.e. for 33 years after the wedding) 195,000 zlotys were not paid until 1720 (i.e. for 33 years after the wedding), while both the spouses and all the parents of the married couple were already dead. This sum was included into inheritance settlements, where the debt was part of the maternal property, and the Orla estate was returned as part of the dowry sum to the paternal property. It seems that the renunciation was a very strong legal argument and allowed the groom’s family for a much stronger bargain position. The lack of fast dowry settlements, even in a longer time perspective, allowed for obtaining much higher sums, in particular if a part of the settlement was real estates given as property or as a pledge.